Overexpression of ARHGAP30 suppresses growth of cervical cancer cells by downregulating ribosome biogenesis. Issue 11 (21st September 2021) - Wu, Aijia; Lin, Lan; Li, Xiao; Xu, Qinyang; Xu, Wei; Zhu, Xiaolu; Teng, Yincheng; Yang, Xiao‐Mei; Ai, Zhihong
Abstract: We aimed to identify whether Rho GTPase activating proteins (RhoGAPs) were downregulated in cervical cancers and might be targeted to reduce the growth of cervical cancer using the GEO database and immunohistochemical analysis to identified changes in transcription and protein levels. We analyzed their proliferation, clone formation ability, and their growth as subcutaneous tumors in mice. To detect ARHGAP30 localization in cells, immunofluorescence assays were conducted. Mass spectrometry combined with immunoprecipitation experiments were used to identify binding proteins. Protein interactions were validated with co‐immunoprecipitation assays. Western‐blot and q‐PCR were applied to analyze candidate binding proteins that were associated with ribosome biogenesis. Puromycin incorporation assay was used to detect the global protein synthesis rate. We identified that ARHGAP30 was the only downregulated RhoGAP and was related to the survival of cervical cancer patients. Overexpression of ARHGAP30 in cervical cancer cells inhibited cell proliferation and migration. ARHGAP30 immunoprecipitated proteins were enriched in the ribosome biogenesis process. ARHGAP30 was located in the nucleous and interacted with nucleolin (NCL). Overexpression of ARHGAP30 inhibited rRNA synthesis and global protein synthesis. ARHGAP30 overexpression induced the ubiquitination of NCL and decreased its protein level in Hela cells. The function of ARHGAP30 on cervical cancer cell ribosome biogenesis and proliferation was independent of its RhoGAP activity as assessed with a RhoGAP‐deficient plasmid of ARHGAP30 R55A . Overall, the findings revealed that ARHGAP30 was frequently downregulated and associated with shorter survival of cervical cancer patients. ARHGAP30 may suppress growth of cervical cancer by reducing ribosome biogenesis and protein synthesis through promoting ubiquitination of NCL. Abstract : ARHGAP30 suppressed growth of cervical cancer by reducing ribosome biogenesis and protein synthesis through promoting ubiquitination of nucleolin.